Pengaruh Lama Distres Kronis Terhadap Perubahan Jumlah Sel Osteoklas Pada Tulang Alveolar Tikus Sprague dawley (The Effect of Chronic Distres Duration on Osteoclast Changes in Alveolar Bone of Sprague dawley Rats) - Cicik Khilar Rizqi; Happy Harmono; Raditya Nugroho (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Chronic distress is a psycho-physiological reaction of stimuli that disrupt homoestasis which cause damage to the body, one of kind is an electrical shock stressor. The distress can increase catecholamines level in considerable amounts and allegedy it produce pro-inflamatory cytokines. Cytokine will affect the Hypoyhalamic pituitary adrenal (HPA) axis to produce cortisol and also act as negative control of cytokines. In this assumption, cytokines can increase bond of osteoclast formation key mediator which is RANKL with its receptor (RANK) to produce osteoclasts. This study was an experimental laboratories research using 8 weeks old Sprague dawley rats with body weight 200-250 gram as samples to observe increase of the number of osteoclasts in the alveolar bone. A total of 32 samples were divided into 4 groups: the rats group exposed with electrical shock stressor for 0, 7, 14, and 28 days. Then samples were processed by tissue processing until it’s ready to observe using an electron microscope with 400x magnification. The results showed that there were significant differences (p <0.05) between groups. It is concluded that the number of osteoclasts alveolar bone osteoclast were increased in Sprague dawley rats that experienced chronic distress. Keywords: stress/distress, cathecolamines, cytokine, cortisol,osteoclast